Proposal for tactics learned in junior high school judo lessons (Part 2): Utilizing "opportunity to use a technique" that can be used in lesson - Ozawa, Y.; Kiyota, K.; Ishibashi, G.; Sakamoto, M.; Ohkawa, Y.; Hirokawa, M.; Na, H. (Association for the Scientific Studies on Judo, Kodokan, 2019)
In this research, we attempted to propose tactics learning in junior high school judo lesson by relating "kata" in junior high school judo class that we have developed as a drill game with "opportunity to use a technique" as a task game in order to connect them to "free practice" which is the main game of judo. Therefore, we attempted to verify the objective effect of "kuzushi" by the action of moving the most basic "tori" fishery (right hand) among "opportunity to use a technique" in junior high school judo lesson.As a result, the center of gravity of "uke" shifted from 3.01 to 3.67 cm, suggesting that the effect had no connection with the degree of judo proficiency.In addition, we adopted the above task game as the lesson for college students in the past three years. In the task game, students compete for the score of "opportunity to use a technique" movement by using "30 second combat exchange practice". As a result, the settlement rate of the game was about 58.7% out of the 46 pairs, and relatively high game characteristics was recognized.From these results, it is plausible to assume that the learning of "opportunity to use a technique" becomes a teaching material for task games where students try to solve the challenge of breaking the opponent`s defensive moves in "free practice."